CERITA GEMPA: ANALISIS TERHADAP STRUKTUR DAN TEMA TEKS - Irna Gayatri D. Ardiansyah (﻿Kantor Bahasa Provinsi Bangka Belitung, 2013)
The writing of knowledge was occur since previous period and it has become the tradition that given to the nextgeneration. In Java, this tradition could be found in primbon form. The notes containt information, so it isimportant to comprehend primbon manuscript text. In Ambon, this tradition can be seen in Cerita Gempamanuscript that containt notes as in primbon. This paper is an attempt to explain primbon and primbonmanuscript in a general manner. Primbon manuscript which used in thi paper is Cerita Gempa. Then, this paperwill discussed analysis of structure and theme in Cerita Gempa manuscript. This paper give description aboutthe content of Cerita Gempa manuscript by explain text’ structure and theme of this manuscript. The structureand theme are analyzed using theory of structural analysis that discussed structure and text theme. Thisqualitative research used descriptive analytic method. The aims of this research is to describe and explainstructure and text theme in Cerita Gempa manuscript. Through the analysis, known that CG manuscript text hastwo texts and three principal ideas with one theme, that is primbon.